OVERVIEW AND ANALYSIS OF METHODS FOR MODELING THE EPIDEMIC DEVELOPMENT PROCESS - Ivashchenko, Daria; Kutsenko, Oleksandr (Bulletin of National Technical University "KhPI". Series: System Analysis, Control and Information Technologies, 2021)
Today, the urgent problem facing humanity is the problem of fighting epidemics and pandemics. One of the ways to solve this problem is the use of mathematical methods for predicting the pandemic process and assessing the impact of measures taken by health authorities to reduce the rate of development of the disease. Based on the analysis of a variety of information sources, the article considers the most effective approach to mathematical and computer modeling of the development of the epidemic on the basis of individually oriented and multi-agent approaches. The analysis of the problem of modeling the development of epidemics on the basis of a multi-agent approach, as well as the possibilities of predicting the course of the epidemiological process is carried out. An example of the structure of a multicomponent simulation model based on the generally accepted verbal model of the spread of viral diseases is given. As an example, the methodology of simulation agent-based modeling using the Any Logic software product of distribution processes 2019-nCoV is considered. The obtained averaged indicators confirmed the main hourly average periods of infection, which were obtained by purely statistical methods. Based on the analysis of published works, the possibilities of managing the development of the epidemic by influencing these factors have been investigated. A relatively simple method of mathematical modeling and forecasting of the epidemic situation has been proposed. It is shown that a timely and adequate forecast is a prerequisite for planning the structure, scale, timing of the necessary measures aimed at preventing epidemics and outbreaks of disease, as well as reducing and eliminating their negative consequences. Keywords: agent simulation, epidemic, math modeling, pandemic, prognostication, simulation.